The need for a triangle comparison among Chinese characters, Pinyin, and English: from behavioral and neurophysiological perspectives - Zhang, Tian; Chen, Zhongmin (Frontiers in Language Sciences, 2025)
The current study reviewed previous research comparing Chinese and English from behavioral and, emphatically, neurophysiological perspectives. We found that previous studies have identified the time course and brain activation locations involved in processing Chinese and English. At the same time, most of them focus on comparing Chinese characters with English or Chinese characters with Hanyu Pinyin, leaving a gap in the comparison between Pinyin and English, which is essential in understanding the relationship between Chinese and English cognition. By summarizing the indices of previous fMRI and EEG studies, we conceived the idea of comparing Hanyu Pinyin and English using a future experimental paradigm. Meanwhile, Pinyin's role in character input and reading development in Chinese children was also an intriguing topic for future research.